2018
DOI: 10.1111/ene.13554
|View full text |Cite
|
Sign up to set email alerts
|

Serum neurofilament light chain in patients with acute cerebrovascular events

Abstract: In conclusion, among patients admitted within 24 h of AIS or TIA onset, admission sNfL levels were associated with clinical severity on admission and TIA diagnosis, but not with infarct size on MR-DWI acquired on admission or functional outcome at 3 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 19 publications
7
63
1
Order By: Relevance
“…Our results are consistent with past studies showing that serum levels of NF-L are higher in people with diverse neurological and neurodegenerative conditions. Researchers have reported that serum levels of NF-L are higher in people with multiple sclerosis (Kuhle et al, 2016;Disanto et al, 2017;Kuhle et al, 2017;Novakova et al, 2017), acute ischemic stroke (De Marchis et al, 2018), active cerebral small vessel disease (Gattringer et al, 2017), familial Alzheimer's disease (Mattsson et al, 2017;Weston et al, 2017), Huntington's disease (Byrne et al, 2017), frontotemporal dementia (Rohrer et al, 2016), Creutzfeldt-Jakob disease (Thompson et al, 2018), Parkinsonian disorders (Hansson et al, 2017), other degenerative ataxias such as multiple system atrophy (Wilke et al, 2018) and amyotrophic lateral sclerosis (Feneberg et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are consistent with past studies showing that serum levels of NF-L are higher in people with diverse neurological and neurodegenerative conditions. Researchers have reported that serum levels of NF-L are higher in people with multiple sclerosis (Kuhle et al, 2016;Disanto et al, 2017;Kuhle et al, 2017;Novakova et al, 2017), acute ischemic stroke (De Marchis et al, 2018), active cerebral small vessel disease (Gattringer et al, 2017), familial Alzheimer's disease (Mattsson et al, 2017;Weston et al, 2017), Huntington's disease (Byrne et al, 2017), frontotemporal dementia (Rohrer et al, 2016), Creutzfeldt-Jakob disease (Thompson et al, 2018), Parkinsonian disorders (Hansson et al, 2017), other degenerative ataxias such as multiple system atrophy (Wilke et al, 2018) and amyotrophic lateral sclerosis (Feneberg et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Because older adults are more likely to have neurological conditions prior to brain injury, NF-L might be elevated differentially in older adults, compared to middle-aged or younger adults, following mild traumatic brain injury (MTBI). A number of studies indicate that serum NF-L levels are higher in people with diverse neurological and neurodegenerative diseases (Kuhle et al, 2016;Rohrer et al, 2016;Byrne et al, 2017;Disanto et al, 2017;Gattringer et al, 2017;Hansson et al, 2017;Kuhle et al, 2017;Mattsson et al, 2017;Novakova et al, 2017;Weston et al, 2017;De Marchis et al, 2018;Feneberg et al, 2018;Thompson et al, 2018;Wilke et al, 2018). Therefore, as a potential diagnostic or prognostic biomarker for neurotrauma, it is important to determine whether there is an association between age and NF-L levels in individuals who sustain MTBIs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, plasma glial fibrillary acidic protein shows > 90% specificity as a biomarker for haemorrhagic stroke, and concentrations are positively correlated with the risk of subsequent clinical deterioration [64]. Neurofilaments are released during neuroaxonal injury [68], including following traumatic brain injury [69], but are also elevated in active cerebral small vessel disease [70] and acute ischaemic stroke [71], particularly in those with higher severity of primary injury [72] and recurrent ischaemic lesions [71]. These markers may prove a valuable avenue of investigation for further studies of END.…”
Section: Recommendationsmentioning
confidence: 99%
“…Elevated levels of neurofilament light chain (NFL) in sera or in the cerebrospinal fluid (CSF) represent neuroaxonal damage and are proposed to have a predictive value concerning outcomes in patients suffering from inflammatory, neurodegenerative, and cerebrovascular diseases …”
Section: Introductionmentioning
confidence: 99%